The Effect of Oral Peer Corrective Feedback Using Youtube on EFL Students’ Writing Skill at Sman 6 Kendari - Ilham, Dewi Suratmi; Nurindah, Nurindah; Alberth, Alberth (Universitas Halu Oleo, 2021)
The aim of this research is to determine the effect of oral peer corrective feedback using YouTube on students’ writing skill at the eleventh grade SMAN 6 Kendari. This research conducted quasi-experimental research design. The sample was 29 students of XI MIA1 which was assigned as experimental group and 33 students of XI MIA2 which was assigned as control group. The research used probability sampling design that is cluster random sampling for taking the sample. The data of this research were collected by giving the students pre-test and post-test in the form of writing test. Then, the data were analyzed by using SPSS 17.00 using descriptive analysis and inferential statistic. The results showed that the mean score of the experimental group was higher than the control group. In the experimental group the mean score of pre-test was 45.72 and the mean score of post-test was 80.82. In comparison, in the control group the mean score of pre-test was 46.79 and the mean score of post-test was 74.28. The result of the independent sample t-test indicated that the value of sig. (2 tailed) which was lower than the significance α value (0.000 < 0.05). In other words, H1 was accepted and it means that there was a significant effect of oral peer corrective feedback by using YouTube on students’ writing skill. Furthermore, the result of the finding also showed that the learning process was also able to increase their knowledge and ideas about the topics they write. The development of ideas and knowledge in explaining topics to be structured into an interesting content.